Analisa Penggunaan Glycol pada Dehydration Unit di Central Processing Plant (CPP) Gundih PT. Pertamina Ep Asset 4 Field Cepu - Hutabalian, Bungka Rico (Action Research Literate, 2025)
Gundih Central Processing Plant (CPP) is a natural gas refinery owned by PT. Pertamina EP Asset 4 Field Cepu. This refinery produces ready-to-use natural gas with a capacity of 45 MMSCFD. To produce ready-to-use natural gas, several stages of the natural gas processing process are needed. The dehydration unit at CPP Gundih is a unit that supports natural gas production. This unit functions to reduce the moisture content of stripping gas with TEG (Triethileneglycol) media. This unit functions to reduce the moisture content of stripping gas with TEG (Triethileneglycol) media. The test parameters for glycol used are Ph, TSS, and H2O content. The use of glycol in the dehydration unit is the main element in absorbing the water content of the gas to be produced. This glycol is divided into 2 states, namely lean glycol and rich glycol. The lean glycol used in the dehydration unit has the specification of the ph max testing parameters. 8,1; TSS max. 100 mg/l and H2O content max. 2%. Then rich glycol has a ph max test parameter specification. 8,1; TSS max. 100 mg/l and H2O content max. 6%. Based on the results of the tests carried out, there was an average lean glycol test at a ph of 11.32; TSS is 37.5 mg/l and H2O content is 1.36%, while rich glycol has an average ph of 11; TSS is 47 mg/l and H2O content is 9.46%.